Acceleration of Electrons and Ions by an ``Almost'' Astrophysical Shock in the Heliosphere - Jebaraj, Immanuel Christopher; Agapitov, Oleksiy; Krasnoselskikh, Vladimir; Vuorinen, Laura; Gedalin, Michael; Choi, Kyung-Eun; Palmerio, Erika; Wijsen, Nicolas; Dresing, Nina; Cohen, Christina; Kouloumvakos, Athanasios; Balikhin, Michael; et al. (Institute of Physics Publishing, 2025)
Collisionless shock waves, ubiquitous in the Universe, are crucial for particle acceleration in various astrophysical systems. Currently, the heliosphere is the only natural environment available for their in situ study. In this work, we showcase the collective acceleration of electrons and ions by one of the fastest in situ shocks ever recorded, observed by the pioneering Parker Solar Probe at only 34.5 million km from the Sun. Our analysis of this unprecedented, near-parallel shock shows electron acceleration up to 6 MeV amidst intense multiscale electromagnetic wave emissions. We also present evidence of a variable shock structure capable of injecting and accelerating ions from the solar wind to high energies through a self-consistent process. The exceptional capability of the probe's instruments to measure electromagnetic fields in a shock traveling at 1% the speed of light has enabled us, for the first time, to confirm that the structure of a strong heliospheric shock aligns with theoretical models of strong shocks observed in astrophysical environments. This alignment offers viable avenues for understanding astrophysical shock processes and the self-consistent acceleration of charged particles.